Peta Ketidaksesuaian Kualifikasi Sektoral di Indonesia - Oktaviana Prayudhani (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2020)
Mismatch is a serious problem in Indonesian labor market. This study aims to determine the qualification mismatch map of the labor mismatch in Indonesia, especially in 5 main sectors with the highest labour force. These sectors are industry, trade, education services, government services and construction. The data used in this study is the BPS National Labour Force Survey (Sakernas) in August 2019. The method used is descriptive statistics through a crosstab table between education level and occupation. The results shows that the qualification mismatch level in Indonesia is 44.8 percent, with 18.83 percent working above their competencies and the remaining 35.48 percent working below competencies. Further, the government administration, defense and social security sectors had the lowest matching rate, which was 25.66 percent. Meanwhile, the sector with the highest matching rate was the education services sector at 72.5 percent.